A Content Analysis On the Quality of Short Stories in Short Stories For Children's Published By Children's Book Trust - Rahmatika, Citra Ayu (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2018)
Reading is one of the language skills. There are four components of the language skills are: listening, speaking, reading, and writing. Reading is one of the important skills in teaching English. In this research, the researcher is interested to discuss about a content analysis on the quality of short stories in short stories for children’s published by children’s book trust. The purpose of this research are to measure the quality of short stories in short stories for children’s published by children’s book trust, and to identify the readability and gender equality of short stories for children’s published by children’s book trust. The design of this research was descriptive qualitative research. To get the data of the research, The researcher used a documentation. The researcher used flesch reading ease formula. The data sources from this research taken from book entitled short stories for children’s published by children’s book trust. In this book consist of 17 titles from 17 authors. Based on the result of the data analysis of documentation, it can be known that all of short story can be read by children from the age 8 – 11 years old. Types of reading level in this short stories are easy and very easy. From the 17 short stories, total number of short stories that tell about men life there were 12. While total number of short stories that tell about women life there were The researcher concluded that the quality of short stories for children’s published by children’s book trust is enough. The readability of short stories in short stories for children’s published by children’s book trust is easily understood by children’s and all short stories are suitable as children’s books. The gender equality in short stories for children’s published by children’s book trust is gender bias. The short stories only focus on one gender. The suggestion are for the readers, the researcher suggest that the readers can selecting to choose short stories which is most suitable to reading. The reader can also apply the result of this study as feedback on their reading activities, improve their knowledge and experience in choosing appropriate book, so that the reader is better in reading skill. For the other researchers, it would be useful for the other researcher to use the result as additional reference for those who want to conduct research. The researcher suggest that the other researchers can add research on the short story